2007
DOI: 10.1159/000112858
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuritis among National Health Insurance Enrollees in Taiwan, 2000–2004

Abstract: Background: The objective was to examine the incidence of optic neuritis in Taiwan. A 5-year longitudinal, nationwide, population-based study was conducted. The participants were a random sample of 191,761 subjects, or about 1% of the enrollees in the National Health Insurance program of Taiwan. Methods: We identified subjects who had at least 1 service claim for ambulatory or inpatient care with a principal diagnosis of optic neuritis between 2000 and 2004. We calculated and statistically analyzed the rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
6
15
0
Order By: Relevance
“…The annual incidence of adult ON requiring intravenous methylprednisolone injection in this study was slightly higher than but similar to the findings of 1.46 and 0.83 per 100 000 people in the former hospital-based studies conducted in Japan (Wakakura et al 1995) and Singapore (Lim et al 2009) and much lower than the 33 per 100 000 people in the Taiwan study performed using National Health Insurance Data (Woung et al 2007). In Western countries, the incidence of ON was between 1.4 and 6.4 per 100 000 people (Percy et al 1972;Jin et al 1998).…”
supporting
confidence: 86%
“…The annual incidence of adult ON requiring intravenous methylprednisolone injection in this study was slightly higher than but similar to the findings of 1.46 and 0.83 per 100 000 people in the former hospital-based studies conducted in Japan (Wakakura et al 1995) and Singapore (Lim et al 2009) and much lower than the 33 per 100 000 people in the Taiwan study performed using National Health Insurance Data (Woung et al 2007). In Western countries, the incidence of ON was between 1.4 and 6.4 per 100 000 people (Percy et al 1972;Jin et al 1998).…”
supporting
confidence: 86%
“…We have previously established the population‐based epidemiological data of motor neuron diseases [20], Creutzfeldt‐Jakob disease and multiple sclerosis [21] in Taiwan from the National Health Insurance Research Database (NHIRD). Other studies utilizing the same database have also been published [22–26]. In this study, we presented the epidemiology data of Wilson’s disease in Taiwan during 2000–2005.…”
Section: Introductionmentioning
confidence: 98%
“…A study done in Korean population showed only 4% of children with MS.[9] Various studies carried out in Southeast Asia in adults had indicated that the clinical profile of ON in these regions may be different from that presented in the Western literature. [1213141516]…”
mentioning
confidence: 99%